Volcanic crisis communication: The case of the Mt. Merapi eruption emergency response - Arif Herfianto; Subhan Afifi; Basuki Agus Suparno (Communications in Humanities and Social Sciences, 2022)
This study aims to explore the local government's implementation of volcanic crisis communication during the emergency response to the eruption of Mount Merapi in Sleman, Yogyakarta, Indonesia. This research used a case study method with a qualitative-descriptive approach and data were collected through interviews, field observations, and documentation. The results of study showed that the implementation of volcanic crisis communication can be explained in terms of information sources, message production and distribution, communication channels, and the affordability and speed of information. During the emergency response period, the Regional Disaster Management Agency has implemented a volcano crisis communication model based on the established standard operating procedures; however, several field findings showed a number of weaknesses in its implementation, such as in the flow of information and communication, which was still very bureaucratic and inflexible, and the lack of complete and fast information. On the other hand, the community has a more straightforward and flexible communication and information system to meet their own information needs regarding the Mount Merapi Eruption disaster. The communication pattern is supported by local wisdom and the role of religious and community leaders who are still believed to be credible sources of information. Communities have also succeeded in establishing independent communication channels to share disaster information by leveraging social networks and traditional media. This research provides an academic and practical contribution to develop the volcanic crisis communication studies in Indonesia.